Sildenafil as a Salvage Treatment for Ovarian Torsion: A Rat Model - Didem Alkas Yaginc; Huriye Ayse Parlakgümüs; Selcuk Yetkinel; Pinar Caglar Aytac; Huriye Eda Ozturan Ozer; Derya Akaydin Aldemir; Esra Bulgan Kilicdag (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: In this study, we aimed to investigate the effect of sildenafil, acting as an anti-oxidant on the ischemic rat ovarian torsion model by pointing out ovarian reserve via AMH levels which is the best marker for oocyte pool. STUDY DESIGN: This study is an experimental animal study conducted according to the principles of the Declaration of Helsinki. Twenty-seven rats were assigned into three groups, each consisting of nine individuals. Group 1: Sham operation (laparotomy only) was performed. Group 2: The torsion group had bilateral torsion and detorsion of the ovaries. Group 3: In Sildenafil and torsion group the rats received 0.7 mg/kg sildenafil (Viagra, Pfizer, New York, ABD) intraperitoneally one hour before torsion and detorsion operation. One month after the initial operation, blood was drawn via the intra-cardiac route, and serum antimullerian hormone (AMH) concentrations were studied. RESULTS: The mean weights of the rats were similar 224 g, 229 g, and 222 g for groups 1, 2, and 3 respectively. Only one rat from Group 2(T/D) died during the experiment leaving eight rats for analysis. The mean value for AMH was 24.9227±12.19124 ng/ml and the mean value for weight was 226.22±19.200. The differences in AMH groups were not statistically significant (p=0.873) CONCLUSIONS: As a result, as is shown in our study, the ovarian reserve may not be influenced by ischemia developed by ovarian torsion or any influences could not change AMH levels. Sildenafil which was given to the rats before detorsion to protect against reperfusion ischemia was found to be ineffective on ovary reserve according to AMH assessment.